Contemporary political ideologies: movements and regimes - Macridis,Roy C. (Boston, 1986)
This third edition of the book that first came out in 1979 is an indication of the vitality of political ideologies and the interest they hold for students. Without ideology we are almost without a conscience, without law and order, without an anchor and a port. But also, without ideology we can have no vision of the other worlds we want to sail to. Ideologies fashion our motivations, our attitudes, and the political regimes under which we live. They shape our values.
Keywords: Political Science-history